Assessing E-Compliance Maturity of Public Procurement Processes in Nigeria (International Journal of Built Environment and Sustainability, 2023)
The manual approach to public procurement is plagued with inefficiencies. To address these problems, efforts were made to digitize the processes in Nigeria. However, the e-compliance readiness of procurement processes is not known. This study attempts to assess e-compliance maturity of public procurement lifecycle in Nigeria. The study adopted a mixed research approach. A qualitative research method was used to establish criteria for evaluating the readiness of public procurement processes for digitization. Focus group interview with Six (6) automation and procurement professionals was conducted to arrive at the parameters used for the readiness assessment. Consequently, a questionnaire survey was administered on experienced public procurement professionals to evaluate the e-compliance readiness of some identified public procurement processes. Best to Worst Method (BWM) was used to evaluate e-compliance maturity level. The study shows that the processes are readily compliant for digitization.
Keywords: Construction Project Management, Construction Cost Management, Rail Projects, Structural Equation Modelling.